'Make Friends with Mexico': The Mexican tourist jacket. Issue 1 (1st October 2015) - Ibarra, Rogelia Lily; Strawn, Susan M.
Mexican tourist jackets entered the United States apparel market as a casual trend among women and little girls after World War II. Blazer-style jackets sewn from woolen fabric featured colourful hand appliquéd and embroidered motifs depicting such iconic Mexican symbols as sarapes, sombreros, burros, desert fauna and dancers. This article traces relationships among symbolic representations of Mexican nationalism on the jackets, development of the post-war tourism industry in Mexico, and subsequent reinterpretation of Mexico as an exotic yet accessible destination for US tourists. Methods included review of literature on post-war tourism to Mexico and examination of extant garments, historical photographs and needlework periodicals. Results reveal that Mexican jackets (originally produced in Mexico) incorporated symbols of Mexican nationalism, especially the emblematic national duo el charro and la china poblana as the dancing couple. An early tourist publication titled 'Make Friends with Mexico' coincided with warming of relations between the two countries and the beginning of American Airlines flights to Mexico in 1943. McCall Needlework appropriated the Mexican tourist jacket in patterns for homemade jackets linked with their origins as souvenirs of Mexico. Analysis of results argues for political motives that encouraged cross-cultural adoption of Mexican symbolism in American fashion. However, this seemingly benevolent cultural exchange through tourism was not equitable; Mexico had to prove itself worthy and familiar to prospective US tourists who associated the country with banditry and tumult. Transforming its image was tantamount to asserting national identity.